Messianic Servant or the End of Israel's Exilic Curses? Isaiah 53.4 in Matthew 8.17. (September 2015) - Watts, Rikk
Contrary to previous suggestions, the use of Isa. 53.4 in Mt. 8.17 does not derive from a desire to portray Jesus either as Isaiah's 'suffering servant' or as Israel's unexpectedly compassionate Davidic messianic king. It comes instead from the gospel writer's conviction that the signal characteristic of Jesus' early ministry – his healing of all who came to him (Mt. 4.23-25; 8.16) – must have divine and therefore scriptural warrant. The only scriptural text that speaks of healing in such comprehensive and eschatological terms is Isa. 53.4. Since Matthew's use of Isaiah elsewhere indicates that he is aware of a verse's larger context, his deliberate truncation of Isa. 53.4 and his translation choices strongly suggest that for him Jesus' divinely authoritative healings (cf. Mt. 9.8) constitute the inauguration, in Jesus' own lifetime, of Yahweh's long-promised removal of covenant curses upon his rebellious and exiled people (Deut. 28.59-61).